Genetic structure of two Plusiinae species suggests recent expansion of Chrysodeixis includens in the American continent. (7th December 2020) - Perini, Clérison R.; Sosa, Verónica I.; Koda, Vicente E.; Silva, Horacio; Risso, Andrés A.; Vasconcelos, Wanessa N. F.; Gonçalves, Carolina F.; Ugalde, Gustavo A.; Machado, Dayanna N.; Bevilacqua, Caroline B.; Ardisson‐Araújo, Daniel M. P.; Maebe, Kevin; et al.
Abstract : The Plusiinae subfamily has many polyphagous species, many of which occur in South America. Chrysodeixis includens and Rachiplusia nu are two representatives that mainly occurs in soybeans, cotton, common beans, sunflower and alfalfa. A population genetic study of C. includens and R. nu collected in the Southern Cone of America was performed using a partial COI gene sequencing data and compared with specimens from other American countries. Six haplotypes were identified in C. includens populations of Brazil, Argentina, Paraguay and Uruguay, organized within a star‐like haplotype network, with the most common haplotype identified as Chin_MC. R. nu populations are more diverse and stable in comparison to C. includens . Populations from Argentina and Uruguay had the highest haplotype diversity, sharing five haplotypes and putatively indicating haplotype exchange. Demographic change analysis suggested a recent population expansion of C. includens over the American continent. Some C. includens haplotypes were country‐specific, suggesting population expansion in the countries where specimens were collected. Abstract : Demographic change analysis indicates a recent population expansion of C. includens populations over the American continent. C. includens haplotypes were country‐specific suggesting population expansion in each country, where cropping systems and pest management differ. Implementations of refuge areas in Bt fields, crop rotation systems, alternation of insecticide mode of action and minimizing pesticide applications can increase the genetic variability of populations.